The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4103/aer.aer_32_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of I-gel versus endotracheal tube in patients undergoing elective cesarean section: A prospective randomized control study

Abstract: Background and Aim:Physiological changes during pregnancy and the sympatho adrenalstimulation during larynoscopy and intubation leads to evaluation of safe devices to secure airway during cesarean section under general anesthesia. I-gel, recently emerging effective supra glottic device found safe during general anesthesia in cesarean section. Aim of the study is to compare the hemodynamic disturbances and airway related complications of I-gel and Endotracheal tube in patients undergoing cesarean section under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…They observed that approximately 20% rise in mean arterial pressure and heart rate seen in endotracheal group when compared with I-Gel group (p<0.001) thus providing greater hemodynamic stability. They concluded remarkable sore throat after endotracheal intubation (p<0.001), however in our study, no obvious incidence of sore throat in recovery was seen in endotracheal group (p=0.500).They compared both groups in terms of postoperative complication of blood on the device, which was not conspicuous in either of the groups consistent with findings of our study 12 .…”
Section: Discussionsupporting
confidence: 88%
“…They observed that approximately 20% rise in mean arterial pressure and heart rate seen in endotracheal group when compared with I-Gel group (p<0.001) thus providing greater hemodynamic stability. They concluded remarkable sore throat after endotracheal intubation (p<0.001), however in our study, no obvious incidence of sore throat in recovery was seen in endotracheal group (p=0.500).They compared both groups in terms of postoperative complication of blood on the device, which was not conspicuous in either of the groups consistent with findings of our study 12 .…”
Section: Discussionsupporting
confidence: 88%
“…The use of SGA in emergency situations such as rescue airway device is easily justifiable as the risks of aspiration outweigh the potential of hypoxaemia and death. However, since 2001, the use of SGA as primary airway device during GA for CD has been demonstrated in several studies and been reviewed on several occasions [8][9][10][11][12][13][14][15][16][17]19,43 && ,44,45 && ,46]. To date, there are at least twelve peer reviewed studies describing the use of SGA as primary airway device (Table 1) [8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Supraglottic Airway Devices As Primary Devices In Obstetric ...mentioning
confidence: 99%
“…In obstetric practice, SGA are confined to use as a rescue airway device when failed intubation occurs [1,7 & ]. More recently, SGAs have been used as the primary airway device for elective and emergency caesarean delivery (CDs) in carefully selected patient cohorts [8][9][10][11][12][13][14][15][16][17][18][19]. This review aims to discuss the place of SGAs in obstetric anaesthetic practice and review the available literature.…”
Section: Introductionmentioning
confidence: 99%
“…27 It provides a more stable haemodynamic profile at insertion with lower mean arterial pressure and heart rate than tracheal intubation in patients undergoing elective Caesarean delivery. 5 Its use in elective Caesarean deliveries has been shown to provide comparable control of the airway (in 9 vs 10 s), 6 but was associated with fewer airway complications, such as bronchospasm, sore throat, regurgitation, and dysphagia. 5,6 Most of the aforementioned studies included fasted nonobese patients and excluded patients with gastrooesophageal reflux or anticipated difficult airway.…”
Section: Supraglottic Airway Devices In Pregnancymentioning
confidence: 99%
“…5 Its use in elective Caesarean deliveries has been shown to provide comparable control of the airway (in 9 vs 10 s), 6 but was associated with fewer airway complications, such as bronchospasm, sore throat, regurgitation, and dysphagia. 5,6 Most of the aforementioned studies included fasted nonobese patients and excluded patients with gastrooesophageal reflux or anticipated difficult airway. Such stringent patient selection criteria were not universal amongst the 11 studies (Table 1).…”
Section: Supraglottic Airway Devices In Pregnancymentioning
confidence: 99%